Immunogenicity and safety of three aluminium hydroxide adjuvanted vaccines with reduced doses of inactivated polio vaccine (IPV-Al) compared with standard IPV in young infants in the Dominican Republic: a phase 2, non-inferiority, observer-blinded, randomised, and controlled dose investigation trial. Issue 7 (July 2017) - Rivera, Luis; Pedersen, Rasmus S; Peña, Lourdes; Olsen, Klaus J; Andreasen, Lars V; Kromann, Ingrid; Nielsen, Pernille I; Sørensen, Charlotte; Dietrich, Jes; Bandyopadhyay, Ananda S; Thierry-Carstensen, Birgit
Summary: Background: Cost and supply constraints are key challenges in the use of inactivated polio vaccine (IPV). Dose reduction through adsorption to aluminium hydroxide (Al) is a promising option, and establishing its effectiveness in the target population is a crucial milestone in developing IPV-Al. The aim of this clinical trial was to show the non-inferiority of three IPV-Al vaccines to standard IPV. Methods: In this phase 2, non-inferiority, observer-blinded, randomised, controlled, single-centre trial in the Dominican Republic, healthy infants aged 6 weeks, not previously polio vaccinated, were allocated after computer-generated randomisation by block-size of four, to receive one of four IPV formulations (three-times reduced dose [1/3 IPV-Al], five-times reduced dose [1/5 IPV-Al], ten-times reduced dose [1/10 IPV-Al], or IPV) intramuscularly in the thigh at 6, 10, and 14 weeks of age. The primary outcome was seroconversion for poliovirus types 1, 2, and 3 with titres more than or equal to four-fold higher than the estimated maternal antibody titre and more than or equal to 8 after three vaccinations. Non-inferiority was concluded if the lower two-sided 90% CI of the seroconversion rate difference between IPV-Al and IPV was greater than −10%. The safety analyses were based on the safety analysis set (randomly assigned participants who received at least one trial vaccination) and the immunogenicity analyses were based on the per-protocol population. This study is registered with ClinicalTrials.gov registration, number NCT02347423 . Findings: Between Feb 2, 2015, and Sept 26, 2015, we recruited 824 infants. The per-protocol population included 820 infants; 205 were randomly assigned to receive 1/3 IPV-Al, 205 to receive 1/5 IPV-Al, 204 to receive 1/10 IPV-Al, and 206 to receive IPV. The proportion of individuals meeting the primary endpoint of seroconversion for poliovirus types 1, 2, and 3 was already high for the three IPV-Al vaccines after two vaccinations, but was higher after three vaccinations (ie, after completion of the expanded programme of immunisation schedule): 1/3 IPV-Al 98·5% (n=202, type 1), 97·6% (n=200; type 2), and 99·5% (n=204, type 3); 1/5 IPV-Al: 99·5% (n=204, type 1), 96·1% (n=197, type 2), and 98·5% (n=202, type 3); and 1/10 IPV-Al: 98·5% (n=201, type 1), 94·6% (n=193, type 2), and 99·5% (n=203, type 3). All three IPV-Al were non-inferior to IPV, with absolute differences in percentage seroconversion for each poliovirus type being greater than −10% (1/3 IPV-Al type 1, −1·46 [–3·60 to 0·10], type 2, −0·98 [–3·62 to 1·49], and type 3, −0·49 [–2·16 to 0·86]; 1/5 IPV-Al type 1, −0·49 [–2·16 to 0·86], type 2, −2·45 [–5·47 to 0·27], and type 3, −1·46 [–3·60 to 0·10]; and 1/10 IPV-Al type 1, −1·47 [–3·62 to 0·10], type 2, −3·94 [–7·28 to −0·97], and type 3, −0·49 [–2·17 to 0·86]). Three serious adverse events occurred that were unrelated to the vaccine. Interpretation: The lowest dose (1/10 IPV-Al) of the vaccine performed well both after two and three doses. Based on these results, this new vaccine is under investigation in phase 3 trials. Funding: Bill & Melinda Gates Foundation.